2
$\begingroup$

I was asked to find two limits.

Let $f$ be differentiable function at $x=1$ and $f(1)>0$.

  • $$\lim_{n \rightarrow \infty}\left(\frac{f\left(1+\frac{1}{n}\right )}{f(1)} \right)^{\frac{1}{n}}$$

Let $\frac{1}{n}=h$ so the limit becomes $$\lim_{h \rightarrow 0}\left(\frac{f\left(1+h \right)}{f(1)} \right)^h=\lim_{h \rightarrow 0} \left(\frac{f(1+h)-f(1)}{f(1)}+1 \right)^h$$

How may I continue?

Same for $\lim_{x \rightarrow 1} \left(\frac{f(x)}{f(1)} \right)^{\frac{1}{\log(x)}}$. I defined $h=\log(x)$ and tried to continue with no luck.

Please help, thank you!

$\endgroup$
2
$\begingroup$

Your approach is correct and it can be continued in the following manner. Let $$g(h) = \frac{f(1 + h) - f(1)}{f(1)}$$ so that $\lim_{h \to 0^{+}}g(h) = 0$ and also note that $\lim_{h \to 0^{+}}g(h)/h = f'(1)/f(1)$. Now we have find the limit $$L = \lim_{h \to 0^{+}}(1 + g(h))^{h}$$ Clearly if we apply logarithms we get

$\displaystyle \begin{aligned} \log L &= \lim_{h \to 0^{+}}\log\{1 + g(h)\}^{h}\\ &= \lim_{h \to 0^{+}}h\log\{1 + g(h)\}\\ &= \lim_{h \to 0^{+}}hg(h)\frac{\log\{1 + g(h)\}}{g(h)}\\ &= 0\cdot 0\cdot 1 = 0\end{aligned}$

so that the answer is $L = 1$.

The second part with $$L = \lim_{x \to 1}\left(\frac{f(x)}{f(1)}\right)^{1/\log x}$$ can be handled similarly. Let us take logs to get

$\displaystyle \begin{aligned}\log L &= \lim_{x \to 1}\frac{1}{\log x}\log\left(\frac{f(x)}{f(1)}\right)\\ &= \lim_{h \to 0}\frac{1}{\log (1 + h)}\log\left(\frac{f(1 + h)}{f(1)}\right)\\ &= \lim_{h \to 0}\frac{h}{\log (1 + h)}\frac{1}{h}\log\{1 + g(h)\}\\ &= \lim_{h \to 0}\frac{h}{\log (1 + h)}\cdot\frac{g(h)}{h}\cdot\frac{\log\{1 + g(h)\}}{g(h)}\\ &= 1\cdot\frac{f'(1)}{f(1)}\cdot 1 = f'(1)/f(1)\end{aligned}$

Hence $L = e^{f'(1)/f(1)}$


Update: In response to some comments I am providing a bit more elaboration. First note that

$\displaystyle \begin{aligned}\lim_{h \to 0}\frac{g(h)}{h} &= \lim_{h \to 0}\frac{f(1 + h) - f(1)}{hf(1)}\\ &= \lim_{h \to 0}\frac{f(1 + h) - f(1)}{h}\cdot\frac{1}{f(1)}\\ &= \frac{f'(1)}{f(1)}\end{aligned}$

Next while taking logarithms we use the logarithms to base $e$. Note that in analysis/calculus the symbol $\log$ always means a natural logarithm and logarithm to other bases have to be indicated explicitly with the base like $\log_{b}a$. Also note the fact that it is only for the natural logarithms to the base $e$ for which the following limit formula holds: $$\lim_{h \to 0}\frac{\log(1 + h)}{h} = 1$$ it does not hold if the base of the logarithm is not $e$.

In fact one can also say that the base $e$ is a "natural" choice for the base of logarithms precisely to make this limit equal to $1$. If the base were something else (like $10$ or some other positive number $a$) then the above limit would not be a simple number like $1$.

$\endgroup$
  • $\begingroup$ Great answer, thanks! $\endgroup$ – Galc127 Dec 27 '13 at 11:30
  • $\begingroup$ Why is $\lim_{h \to 0^{+}}g(h)/h = f'(1)/f(1)$ ? $\endgroup$ – GinKin Dec 28 '13 at 14:33
  • $\begingroup$ Also, $L = e^{f'(1)/f(1)}$ ? it could have been any base it doesn't have to necessarily be e right ? $\endgroup$ – GinKin Dec 28 '13 at 15:15
  • $\begingroup$ @GinKin: I have provided more explanation in my answer. Hope it helps to answer your queries. $\endgroup$ – Paramanand Singh Dec 29 '13 at 3:56
  • $\begingroup$ Thanks for the explanation. I thought that just log mean base 10 and only ln means the natural log... $\endgroup$ – GinKin Dec 29 '13 at 20:00
2
$\begingroup$

You can also write $f(x)=f(1)+f'(1)(x-1)+o(x-1)$ as $x \to 1$. In the second limit this leads to $$ \left[ \left( 1+ \frac{f'(1)}{f(1)}(x-1)+o(x-1) \right)^{\frac{f(1)}{f'(1)}\frac{1}{x-1}} \right]^{\frac{x-1}{\log x}} $$ and you can use $\lim_{\varepsilon \to 0} \left(1+\varepsilon \right)^{\frac{1}{\varepsilon}}$.

$\endgroup$
0
$\begingroup$

In your first question , just substitute h in the 2nd last step from where you will get the limit as 1.

Your second question is of the form $1^{\infty}$.

Hint: If limit of ${f(x)}^{g(x)}$ is of the form $1^{\infty}$ ,then

limit = $\lim e^{(f(x) - 1)g(x)}$

$\endgroup$
  • $\begingroup$ First, thank you for your answer. Second, I still don't get it. There is no need of using derivatives? It seems that I can just plug in h=0 in the first step after subsitute $h=\frac{1}{n}$... And I really don't understand what you wrote about the second limit. $\endgroup$ – Galc127 Dec 25 '13 at 18:24
  • $\begingroup$ @Galc127 $a^x = e^{x ln(a)}$. You must be familiar with this. $\endgroup$ – user2369284 Dec 25 '13 at 18:27

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.